The concept of KH. Ahmad Dahlan in the Development of Egalitarian Islam: Konsep KH. Ahmad Dahlan dalam Pengembangan Pendidikan Islam Egalitarian - Sita, Desita; Haryanto, Budi (Universitas Muhammadiyah Sidoarjo, 2022)
Ahmad Dahlan's concept in developing a school in which general science and religious knowledge are taught at the Muhammadiyah School aims to form intellectual scholars by dissolving social class barriers applied by the Dutch education system which is counter-egalitarian in the world of education which causes differences in school graduates. resulting from each of these educations. Ahmad Dahlan's struggle in helping to change the fate of indigenous peoples embraced the common people by providing free schools in which there was general knowledge and religious knowledge aimed at changing their social status for the better. In order for the ideas implemented by Ahmad Dahlan to remain sustainable, the Muhammadiyah organization was formed as a conduit for his concept of thought. The concept of educational thought and business charity founded by Ahmad Dahlan continues and is growing, managed and continued by Persyarikatan Muhammadiyah. Muhammadiyah schools are not only spread throughout Indonesia but also abroad until now.